How can HIV/STI testing services be more accessible and acceptable for gender and sexually diverse young people? A brief report exploring young people's perspectives in Queensland. (19th June 2019) - Heard, Emma; Oost, Ellen; McDaid, Lisa; Mutch, Allyson; Dean, Judith; Fitzgerald, Lisa
Abstract: Issue addressed: Gender and sexually diverse young people (GSDYP) are an important target group for HIV/sexually transmitted infection (STI) prevention and there is an immediate need to explore ways to make testing interventions accessible and appropriate for this group. Methods: We used a modified World Café workshop with 14 GSDYP in Brisbane Australia, to inform the development of a pilot community‐based testing intervention. Results: The workshop identified the key features of an ideal service, which would include multiple, accessible sites that offer holistic, affordable services and confidential care by respectful and knowledgeable providers. The service would allow young people to engage in decision‐making processes, have a culturally inclusive, comfortable and friendly atmosphere, and provide free sexual and reproductive health technologies. Conclusion: When designing HIV/STI testing interventions for key groups, health promotion practitioners need to be cognisant of localised and nuanced expectations and ensure that services are tailored to the needs and experiences of the local population. So what?: This study provides insights into the needs and expectations of HIV/STI testing interventions for GSDYP in Australia, a key at‐risk group whose perspectives are not adequately voiced in sexual health research and intervention design. Summary: This study explores facilitators and current barriers to HIV/STI testing with a group of gender and sexually diverse young people in Brisbane, Australia. Outcomes provide insights into the needs and expectations of HIV/STI testing services for this group.